ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL DALAM MENUNJANG EFEKTIVITAS SISTEM PEMBERIAN KREDIT (Studi pada KSP Kopdit Pintu Air di Desa Ladogahar Kecamatan Nita) - Libu Lamawitak, Paulus; Francina Siba, Maria (Accounting UNIPA - Jurnal Akuntansi, 2022)
This study aims to determine the application of the internal control system in supporting the effectiveness of the credit provision system on Pintu Air Credit Union. The data collection technique used in this study was an interview technique while the data analysis technique used was a descriptive analysis technique by comparing the internal control system that has been applied in Pintu Air Credit Union with the actual system according to COSO. The result of this study indicate that the application of internal control system in supporting the effectiveness of the crediting system implemented by Pintu Air Credit Union does not fully meet the five elements of the internal control system according to COSO, the element that is not appropriate is the monitoring and internal control system in supportingthe effectiveness of the lending system at Pintu Air Credit Union has been effective